Formation mechanism of the oolong tea characteristic aroma during bruising and withering treatment. (15th December 2018) - Hu, Ci-Jie; Li, Da; Ma, Yi-Xiao; Zhang, Wei; Lin, Chen; Zheng, Xin-Qiang; Liang, Yue-Rong; Lu, Jian-Liang
Graphical abstract: Highlights: Bruising and withering significantly increase the released and remaining volatiles. High ratio of terpenoids to green leaf volatiles was a key character of oolong tea. Increased volatiles might be largely generated through de novo synthesis. Aroma formation was modulated by up-regulating expression of the relevant genes. Abstract: To elucidate formation mechanism of oolong tea aroma, the released and remaining volatiles during bruising and withering treatment were analyzed using head space solid-phase microextraction/gas chromatography-mass spectrometry. An increase in proportion of the released terpenoid volatiles (TVs) along with a decrease in proportion of the released C6 green leaf volatiles (GLVs) was observed in both cultivars 'Zhejiang139' and 'Foshou'. Proportion of remaining TVs also fluctuated reversely with GLVs although the level of these volatiles increased remarkably. High ratio of TVs to GLVs was the key chemical foundation of oolong tea characteristic aroma and could be regarded as a good indicator in screening cultivar for suitably producing high quality oolong tea. Combining with transcriptome analysis, increased TVs and GLVs during the treatment might be largely generated through de novo synthesis and modulated at transcript level through up-regulation of genes involved in terpenoids metabolism and enzymatic cleavage of long-chain fatty acids.